A parametrização do controle de constitucionalidade de políticas públicas de infraestrutura por meio dos objetivos fundamentais da República: o contributo do desenvolvimento nacional e do combate às desigualdades regionais à hermenêutica constitucional - Gondim, Liliane Sonsol (2021)
The purpose of this thesis is to provide a suitable tool for a judicial review of public infrastructure policies using the fundamental objectives of the Republic national development and regional inequalities whose economic character shows their ability. It requires a change of perspective from Law to the Economics Science. The intention is to enlarge the cognitive horizon of the constitutional interpreter. For the fulfillment of the objectives, the complex systems theory is used to discuss the relations between Law and Economics Science. The objectives are decomposed into two dimensions, legal and economic, recognizing their principal aspect, which imposes their observance to the entire legal system, as well as their economic aspect, configuring them as base metrics to assess public infrastructure policies. Public infrastructure policies are conceptualized, revealing their role in the construction of the Brazilian State. Finally, the Normative Impact Analysis is approached as an instrument that can be used both by the creator of public policies and by the Judiciary in the exercise of judicial review. The methodology to be used is part of the inductive method, through the analysis of public policies rules and bibliographical research. It is possible to identify law elements that increase regional inequalities, that harms constitutional principles, leading to the possible identification of an unconstitutional state of affairs. It is necessary assistance of several specialized institutions to implement a concentrated dialogical control procedure.